2011
DOI: 10.5897/ajpp11.204
|View full text |Cite
|
Sign up to set email alerts
|

Department of Tea Science, Zhejiang University, Hangzhou 310058, P. R. China.

Abstract: To investigate the regulatory role of RhoA/Rho kinase in the effects of fluvastatin (Flu) on the tumor necrosis factor-(TNF-) induced expression of tissue factor (TF) in human umbilical vein endothelial cells (HUVECs) which may provide basis for the prevention of arterial thrombosis, HUVECs in logarithmic phase were divided into TNF-group, Flu group and TNF-+Flu group. enzyme-linked immunosorbent assay (ELISA), real time polymerase chain reaction (RT-PCR) and western blot assay were employed to detect the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…The apparent viscosities of CWS-Na and CWS-K increased slightly compared with that of CWS. The findings can be attributed to Na + and K + that were attracted by the negative charges on the coal surfaces, which compressed the double electric layer and reduced the negative charges on these coal surfaces, weakened the electrostatic repulsion between coal particles, and enabled the coal particles to easily agglomerate . The findings also indicate that although the Na + and K + contents in wastewater were high, their effects on the properties of CWS are minimal.…”
Section: Resultsmentioning
confidence: 94%
“…The apparent viscosities of CWS-Na and CWS-K increased slightly compared with that of CWS. The findings can be attributed to Na + and K + that were attracted by the negative charges on the coal surfaces, which compressed the double electric layer and reduced the negative charges on these coal surfaces, weakened the electrostatic repulsion between coal particles, and enabled the coal particles to easily agglomerate . The findings also indicate that although the Na + and K + contents in wastewater were high, their effects on the properties of CWS are minimal.…”
Section: Resultsmentioning
confidence: 94%
“…At the same time, the distribution in the FL was significantly reduced. Lu et al [ 24 ] showed that amino acids such as proline or histidine in proteins could bind to polyphenol molecules through hydrophobic forces, and intermolecular hydrogen bonds could further enhance the binding. Among them, casein preferred to bind to highly polymerized polyphenols, whereas lactic protein preferred to bind to small molecular polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…Political communication during mobilization has been a noticeable strength or symbol of the CPC: early during war time, a publicity team was set up in each troop of the red army, publicity organization set up in each hierarchical level of government in anti-Japanese base area; both routine activity and military activity were integrated with propaganda discourse; there were various forms of media such as announcements, pamphlets, slogans, wall newspapers, and journals (Jiang, 2011: 60). Some of the procedures and discourse structures have been retained after the establishment of new China.…”
Section: Political Communication In Mobilizationmentioning
confidence: 99%
“…The process of top-down mobilization in contemporary China was inferred as follows: First, an official document is released by the central committee or the state council or in the form of an editorial or commentator’s article in People’s Daily (China’s official newspaper); second, the information is transmitted hierarchically inside the bureaucratic system; the third step is to transfer the information or requirement mostly from the local cadres to the ordinary people; the last step is to set up certain good examples or role models effectively carrying out the policy (Wang, 2006). In such a process, the communication inside the bureaucratic system is characterized as that the policies are made after careful consideration by the top government, and then required to be efficiently transformed and rigidly carried out; the communication between government and the public is characterized as emphasizing and reinforcing the importance of certain argument and ways to realize the goal (Jiang, 2011: 172–173). To achieve the goal and customize the information for the populations with relatively low levels education, the communication style is generally explicitly informal one with a conversational tone, such as the simplification of principles into catchy phrases and numbers so that they can be memorized by the public (Jiang, 2011; Townsend and Womack, 2003: 152).…”
Section: Political Communication In Mobilizationmentioning
confidence: 99%